Obtenção e caracterização de um compósito de matriz de resina poliéster e pó de resíduo de aço - Spinelli, Mário César de Oliveira (2022)
The growing use of organic products and varied processes of environmental processing of products and their consequences for human and varied health of the planet. Among the material machining processes, it is produced by machining processes, which are more harmful to human health, and that cause environmental concern. The processes for obtaining and characterizing deposits with polyester resin (RP) and iron powder filler (PRA) were studied. Composites and resins were determined by the resin mass ratio 1.0 RP + 0.50 PRA, 1.0 RP + 1.0 PRA and 1.0 RP + 1.5 PRA. The base fabrication method or closed bond molding was done cold. As proposed composite configurations. All designed formulations can be processing. Such compounds were properties characterized by the determination of their mechanical, thermal, electromagnetic, density, water absorption and aging. The composites obtained will be used for electromagnetic shielding. The composite with the highest economic viability was 1.0 RP + 1.5 PRA. It was found that the PRA was composed of 98% iron and that it had the function of filling and flexing load and reinforcement for impact, where the composite had its most promising result. The composite achieved a shielding factor of approximately 23 decibels at the 9 GHz frequency, in the X-band, its capability for electromagnetic shielding.